A STUDY EFFECT OF LEARNING COGNITIVE GUIDED INSTRUCTION AND THINK - PAIR - SHARE TECHNIQUE IN INEQUALITY ON THE MATHEMATICAL PROBLEMS SOLVING ABILITY AND MATHEMATICAL COMMUNICATION ABILITY OF NINTH GRADE STUDENTS - Intharach, kulisara; Sumirattana, Sunisa (Journal of MCU Nakhondhat, 2023)
The purposes of this research were 1) to compare mathematical problem - solving ability and the mathematical communication ability of Mathayomsuksa III students on the subject of the inequality before and after obtaining Cognitive Guided Instruction and Think - Pair - Share technique 2) to compare mathematical problem - solving ability and the mathematical communication ability of Mathayomsuksa III students on the subject of the inequality obtaining Cognitive Guided Instruction and Think - Pair - Share technique with the criterion of 70%. The subjects of the study were 31 Mathayomsuksa III students. They were randomly selected by using cluster random (Cluster Random Sampling). The instrument use in data collection were 1) Teaching Plan Mathayomsuksa III students on the subject of the inequality 2) The mathematics problem - solving abilities and mathematical communication competency test. The data were statistically analyzed by using t - test for independent samples. The finding were as follows: 1) The mathematics problem-solving ability of the experimental group after obtaining Cognitive Guided Instruction and Think - Pair - Share technique on the subject of the inequality was statistically higher than before learning and statistically higher than 70 percent criterion at the .05 level of significance. 2) The mathematics communication ability of the experimental group after obtaining Cognitive Guided Instruction and Think - Pair - Share technique on the subject of the inequality was statistically higher than before learning and statistically higher than 70 percent criterion at the .05 level of significance.